Trajectories of adaptive and disturbed identity dimensions in adolescence: developmental associations with self-esteem, resilience, symptoms of depression, and borderline personality disorder features - Bogaerts, Annabel; Claes, Laurence; Raymaekers, Koen; Buelens, Tinne; Bastiaens, Tim; Luyckx, Koen (Frontiers in Psychiatry, 2023)
To advance our understanding of adolescents’ identity formation and how it may play into their psychological functioning, this study investigated developmental trajectory classes of adaptive and disturbed dimensions of identity formation, and whether adolescents belonging to different trajectory classes develop differently on self-esteem, resilience, symptoms of depression, and borderline personality disorder (BPD) features. Three-wave longitudinal data from 2123 Flemish adolescents was used (54.2% girls; Mage = 14.64, range = 12-18 at T1). Results pointed to four trajectory classes of identity formation: adaptive identity, identity progression, identity regression, and diffused identity. The adaptive identity class presented with stable high levels of self-esteem and resilience, and stable low levels of symptoms of depression and BPD, whereas opposite results were obtained for the diffused identity class. The identity progression class reported an increase in self-esteem and resilience as well as a decrease in symptoms of depression and BPD, whereas opposite results were obtained for the identity regression class. These results emphasize that adaptive and disturbed dimensions of identity formation are closely related to markers of well-being and psychopathology among adolescents, and could help identify adolescents with an increased risk for negative psychological functioning or increased opportunity for positive psychological functioning.